HUBUNGAN TINGKAT PENGETAHUAN ORANG TUA DENGAN TINGKATKEMANDIRIAN ANAK KELAS 1 SD DI SDN GAMPING 1 KECAMATAN KRIANKABUPATEN SIDOARJO - Rahmawati, Ima; Ma’rifatul A, Lilik (JURNAL KEPERAWATAN BINA SEHAT, 2009)
Self supporting is kind of or conditon that self contained without depend on another person. Based on development task of school child, a child is self-supporting if they have had the abillity how to helps themselves (self-help). To achieve the self supporting, child must optimize self supporting that make possible to them to do everything for themselves. Doing the development task and child self supporting needs parents guidance. while doing guidance needed good erudition so that parents can threat child correctly. The aims of this research is analyzing connection of parent’s erudition level with First grade of elementary school.The design’s research uses correlation with approach cross sectional. Parents population and First grade of elementary school sample technique uses technique Purposive Sampling. Instrument that used questioner and observation sheet. Analysis Data uses Spearman Rho test. Analysis Data result shows level significant r = 0,000 < 0.05. Coefficient correlation 0,683 that mean found strong connection between parents erudition level with child self supporting level.To be a self-supporting a child want to chance, family support and with environment surrounding them. In the family, parent have role to impersonates guide, and the aim of self-supporting child. Parents role is the most influence in the Development of child self supporting, and parents must do cooperation with the teacher to give suitable punishment that is done by the child.Keyword: erudition, self supporting, parents, child.